PENGARUH WATER RESOURCES SECTOR ADJUSTMENT LOAN (WATSAL) TERHADAP PEMENUHAN HAK ATAS AIR DI INDONESIA - Ananda, Patria Rizky; Utomo, Tri Cahyo (Journal of International Relations, 2019)
Water Resources Sector Adjustment Loan (WATSAL) was proposed by the World Bank to the Government of Indonesia to overcome the economic crisis of 1997-1998. In order to fulfill the requirements in WATSAL, the Indonesian Government passed Law No. 7 of 2004 concerning Water Resources (Water Resources Law). This law raises pros and cons because it gives the opportunity for the private sector to participate in water resources management (water privatization) which is contrary to Article 33 Paragraph (3) of the 1945 Constitution. This research explain how WATSAL influences on the fulfillment of right to water in Indonesia. In line with that, this research aims to determine the influence of WATSAL on fulfilling the right to water in Indonesia. The researcher uses the type of explanatory research by collecting data from desk research and field research techniques in the period of research in 2004-2015. This research uses the framework of Neo-Marxism thought adopted by Steans and Pettiford. The result of this research shows that WATSAL affects the fulfillment of the right to water in Indonesia. The case study used to support this argument is the existence of the bottled water industry (AQUA Group) which has a role in discriminating against the right to water and causing water sources for the residents around it (Sukabumi and Klaten) to dry up